2019
DOI: 10.1016/j.jbiotec.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Production, purification and characterization of an elastin-like polypeptide containing the Ile-Lys-Val-Ala-Val (IKVAV) peptide for tissue engineering applications

Abstract: Elastin-like polypeptides (ELPs) are biocompatible-engineered polypeptides, with promising interest in tissue engineering due to their intrinsic biological and physical properties, and their ease of production. The IKVAV (Ile-Lys-Val-Ala-Val) laminin-1 sequence has been shown to sustain neuron attachment and growth. In this study, the IKVAV adhesion sequence, or a scrambled VKAIV sequence, were incorporated by genetic engineering in the structure of an ELP, expressed in Escherichia coli and purified. The trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The 1:1 IKVAV:ELR ratio, or 60% w/w, was selected based on a previous study by Pavia dos Santos et al., which showed that a 20% w/w IKVAV ELR concentration (in reality 40%, as each ELR backbone contains two IKVAV domains) resulted in longer neurite formation than those containing 10% or 5% IKVAV‐ELR. [ 33 ] An NHS‐Cyanine 5 fluorescent probe (Jena Bioscience GmbH, Germany) was 1:1 conjugated to the RGD‐azide‐ELR and VKV‐cyclooctyne‐ELR to produce the RGD‐azide‐Cy5‐ELR and VKV‐cyclooctyne‐Cy5‐ELR. De novo produced ELRs, namely VKV‐azide‐ELR, VKV‐cyclooctyne‐Cy5‐ELR, RGD‐azide‐IKVAV‐ELR, and RGD‐azide‐Cy5‐ELR, were characterized by proton nuclear magnetic resonance (1H‐NMR), matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR) (Figures S6–S21, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…The 1:1 IKVAV:ELR ratio, or 60% w/w, was selected based on a previous study by Pavia dos Santos et al., which showed that a 20% w/w IKVAV ELR concentration (in reality 40%, as each ELR backbone contains two IKVAV domains) resulted in longer neurite formation than those containing 10% or 5% IKVAV‐ELR. [ 33 ] An NHS‐Cyanine 5 fluorescent probe (Jena Bioscience GmbH, Germany) was 1:1 conjugated to the RGD‐azide‐ELR and VKV‐cyclooctyne‐ELR to produce the RGD‐azide‐Cy5‐ELR and VKV‐cyclooctyne‐Cy5‐ELR. De novo produced ELRs, namely VKV‐azide‐ELR, VKV‐cyclooctyne‐Cy5‐ELR, RGD‐azide‐IKVAV‐ELR, and RGD‐azide‐Cy5‐ELR, were characterized by proton nuclear magnetic resonance (1H‐NMR), matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF), differential scanning calorimetry (DSC), and Fourier transform infrared spectroscopy (FTIR) (Figures S6–S21, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%
“…Amongst the genetically encoded polymeric sequences, ELPs (elastin-like polypeptides), also known as elastin-like recombinamers (ELRs), have been widely used for the development of thermosensitive block copolymers for several biomedical applications, mainly for release systems and tissue engineering [232][233][234][235][236][237][238]. Elastin-like polypeptides can undergo reversible phase transition induced by pH, temperature, or ionic strength, whose transition phase is directly dependent on the ELP's sequence transition temperature (Tt).…”
Section: Advanced Polymersmentioning
confidence: 99%
“…ThT assay confirmed the presence of amyloid fibrils formed from the IKVAV sequence. Both in vitro and in vivo experiments demonstrated that the hydrogel promoted the growth of sensory neuron without noticeable cytotoxicity and inflammatory effects [ 126 ]. Deidda et al fused the amyloid peptide NSGAITIG from adenovirus fiber shaft to the RGD motif [ 127 ].…”
Section: Macroscopic Functional Amyloid Materialsmentioning
confidence: 99%